Corporate Storytelling as an Effective Communication Tool - Serena Camilla Crocchi (Quaderni di Linguistica e Studi Orientali, 2019)
This paper proposes to highlight the effectiveness of storytelling as a powerful and persuasive communication tool in the corporate context. This peculiar kind of communicative approach allows the creation of a symbolic universe potentially shared by the public, with which not only can it recognize itself, but with which it can actually interact. The fundamental theories of narration and their evolution are taken into consideration, as well as the evolution of the consumer into prosumer and the sociological and economic consequences emerged. In the present paper we will discuss two case studies: Wind: Papà – an example of a short film with a strong emotional impact on the audience and a revolutionary message – and Léon Vivien: Facebook 1914 – a masterful example of how narrative content can be exploited using different mediums and the potential of social networks.